2015
DOI: 10.1007/s12602-015-9199-1
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of Genome-Wide Screening for Biosafety Assessment of Probiotics: A Case Study of Lactobacillus helveticus MTCC 5463

Abstract: Recent years have witnessed an explosion in genome sequencing of probiotic strains for accurate identification and characterization. Regulatory bodies are emphasizing on the need for performing phase I safety studies for probiotics. The main hypothesis of this study was to explore the feasibility of using genome databases for safety screening of strains. In this study, we attempted to develop a framework for the safety assessment of a potential probiotic strain, Lactobacillus helveticus MTCC 5463 based on geno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(18 citation statements)
references
References 39 publications
0
18
0
Order By: Relevance
“…saniviri . Unsurprisingly, there are many reports about Hemolysin and its safety in Lactobacilli [74, 75]. These reports suggested that Lactobacilli can be included in probiotic products without any danger to the host organism [1, 7477].…”
Section: Resultsmentioning
confidence: 99%
“…saniviri . Unsurprisingly, there are many reports about Hemolysin and its safety in Lactobacilli [74, 75]. These reports suggested that Lactobacilli can be included in probiotic products without any danger to the host organism [1, 7477].…”
Section: Resultsmentioning
confidence: 99%
“…For the probiotic strain Lactobacillus helveticus MTCC5463, safety related genes were categorised into resistome, heavy metals, adverse metabolic genes, virulence related genes, and stress related genes [27], and the presence or absence of genes in these categories were used to aid the safety assessment of this strain. A similar approach was used for another gram-positive probiotic strain, Bacillus coagulans GBI-30, 6086 [28].…”
Section: Other Available Tools To Assess the Safety Of Fcmentioning
confidence: 99%
“…Given the separate approaches in screening probiotic bacterial strains, multiple independent studies have demonstrated several methods in screening different probiotic strains for antibiotic resistance genes (Tompkins et al, 2008; Vankerckhoven et al, 2008; Chang et al, 2009; Galopin et al, 2009; Xiao et al, 2010; Klein, 2011; Nueno-Palop and Narbad, 2011; Cebrián et al, 2012; Songisepp et al, 2012; Wei et al, 2012; Tan et al, 2013; Devi et al, 2015; Senan et al, 2015). In places where it is not bound to either US FDA or EFSA, screening for antibiotic resistance genes in probiotic strains becomes even more important as rigid guidelines and regulations for probiotic use are lacking (Chang et al, 2009).…”
Section: Safety Of Probiotic Usementioning
confidence: 99%
“…Included in this group are Lactobacillus and Enterococcus. Both genera are currently extensively screened for species that can be used as probiotic bacteria (Tompkins et al, 2008; Vankerckhoven et al, 2008; Chang et al, 2009; Klein, 2011; Nueno-Palop and Narbad, 2011; Cebrián et al, 2012; Songisepp et al, 2012; Tan et al, 2013; Devi et al, 2015; Senan et al, 2015). …”
Section: Safety Of Probiotic Usementioning
confidence: 99%
See 1 more Smart Citation